Engaging Secondary School Students in the Strategy of Vocabulary Self-Collection Strategy for Learning General Vocabulary: A Classroom Action Research: English - Alip Nurahman Sudarmaji; Elih Sutisna Yanto (Prodi Tadris Bahasa Inggris, 2023)
The objective of this study was to investigate the efficacy of the Visual Semantic method (VSS) in enhancing students' acquisition of general vocabulary, as well as to document the reactions of junior high school students towards the use of the VSS method in their vocabulary learning process. The present study employed a qualitative approach, utilizing classroom action research (CAR) as the chosen research design. The data collection methods employed by the author encompassed observation, interviews, and documentation. The present study was carried out at a junior high school located in Indonesia. The observation took place in a single classroom. The participants in this study consisted of six students enrolled in the class. The results of the study indicated that the implementation of the Vocabulary Self-Selection (VSS) strategy resulted in favorable outcomes in terms of student engagement. Specifically, students exhibited increased levels of activity and autonomy in their efforts to comprehend unfamiliar words. Moreover, students displayed a heightened curiosity towards previously unknown vocabulary encountered in the text. Additionally, the classroom environment fostered a more collaborative approach to learning. Furthermore, the students expressed a belief that engaging in group discussions proved to be highly significant as it facilitated their completion of the VSS group chart and enhanced their comprehension of the book. Regarding the challenges encountered by students in vocabulary acquisition through the use of VSS, several obstacles were identified. Firstly, students reported encountering a large number of unfamiliar words, which hindered their progress. Additionally, they expressed difficulty in comprehending the meaning of words within the context of the text. Furthermore, students acknowledged that they were encountering vocabulary that had not been previously taught in their educational curriculum, resulting in a time-consuming process of deciphering the meanings of these unfamiliar terms.